Post-Judicial Review of Article 433: The Position of Persons with Disabilities in Making Agreements - Faradigma D Zainuddin (Fox Justi : Jurnal Ilmu Hukum, 2026)
Constitutional Court Decision No. 93/PUU-XX/2022 has fundamentally changed the construction of legal capacity for persons with disabilities in the Indonesian civil law system, which for more than a century and a half has been dominated by a discriminatory substitute guardianship regime. This study aims to analyze the transformation of legal capacity norms for persons with disabilities following the decision and examine the operationalization of the supported decision-making paradigm in contract law in Indonesia. This research is a normative legal study with a legislative approach, a conceptual approach, and a case approach. The results show that the Constitutional Court decision has given rise to three fundamental transformations: first, a change in the nature of guardianship from imperative ("must") to facultative ("can"), which opens up room for judicial discretion; second, the elimination of the stigmatizing terminology of "dumb, brain-sick, or dark-eyed" to "person with mental and/or intellectual disabilities"; third, recognition of the episodic nature of mental disabilities, which allows for a case-by-case assessment of capacity. This transformation aligns with the global paradigm shift from substituted decision-making to supported decision-making mandated by the CRPD. However, its implementation in contract law faces serious challenges related to the lack of legal parameters, the validity of the agreement, and the role of notaries. Legal construction is needed that integrates the principle of supported decision-making through voluntary assistance institutions and changes in the mindset of law enforcement officials and the public so that people with disabilities can fully participate as autonomous legal subjects in civil law.